2021
DOI: 10.1007/978-981-16-0119-4_44
|View full text |Cite
|
Sign up to set email alerts
|

Design Thinking as a Strategy to Inculcate Problem-Based Learning (PBL) in Undergraduate Education Across South Asian Universities

Abstract: The Bologna declaration states that, "successful learning and studying in higher education should involve students in deep learning". However, a survey of faculty across institutes in Nepal and Bhutan highlights that the undergraduate students in engineering and management lack skills needed to be industry-ready. They face difficulty in getting employed after graduation and if placed, then struggle during their employment due to insufficient practical experience, lack of good communication skills and unawarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…As a process, it is rooted in constructivism and the overarching approach has been collated into12 steps (as in Figure 1). (Acharya, et al, 2021a). Acharya, et al (2021a) highlights that the top constraints with respect to the context are; heavy syllabi as per University-directed lesson plans that restricts time for practicals and less number of co-instructors to help guide practicals.…”
Section: Theoretical Underpinningmentioning
confidence: 99%
See 4 more Smart Citations
“…As a process, it is rooted in constructivism and the overarching approach has been collated into12 steps (as in Figure 1). (Acharya, et al, 2021a). Acharya, et al (2021a) highlights that the top constraints with respect to the context are; heavy syllabi as per University-directed lesson plans that restricts time for practicals and less number of co-instructors to help guide practicals.…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…(Acharya, et al, 2021a). Acharya, et al (2021a) highlights that the top constraints with respect to the context are; heavy syllabi as per University-directed lesson plans that restricts time for practicals and less number of co-instructors to help guide practicals. In addition, it was found that these faculty members and administrators were unfamiliar with PBL pedagogy and how to imbibe the same into their respective subjects/courses, and therefore, a two-pronged solution was devised to empower them with Capacity and Resources, as articulated below in (Figure 2).…”
Section: Theoretical Underpinningmentioning
confidence: 99%
See 3 more Smart Citations